The Tragedy of Migration in Azra Asghar Short Stories: عذرااصغر کے افسانوں میں ہجرت کاالمیہ - Naqvi, Dr. Sadaf; Waheed, Mehnaz (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
Azra Asghar has interpreted the living life of her surroundings. She always eyed on the human conflict & aggravating circumstances. After the partition of Pakistan, the situation was completely changed. People came to Pakistan after the hardships of migration & leaving behind their homes. Azra Asghar's family also came to Pakistan after migration. Being a sensitive person, she could not remain unaffected by these situations. Her short stories carry the sorrow of migration & the inflicted sorrow of changing human behaviors.